Strategies Adopted for Enrolling Girls in Kasturba Gandhi Balika Vidyalayas Managed by Different Agencies in Gujarat An Exploratory Study - Srivastava, Gouri (JOURNAL OF INDIAN EDUCATION, 2015)
The Kasturba Gandhi Balika Vidyalaya Scheme is a promising and successful initiative of the Government of India. It is an integral part of SSA programme. The scheme provides second chance of formal residential schooling facility to out-of-school girls belonging to the most marginalised and hard to reach groups. Located in the Educationally Backward Blocks of twenty-seven states of India, it attempts to fulfil the Constitutional mandate of providing elementary schooling to girls, herby reducing gender gaps at this crucial stage of education. It is specially designed for SC, ST, OBC, Minorities, BPL and for girls facing different physical disabilities. The scheme is being implemented by SSA, NGO’s and the Mahila Samakhya Society. In the present paper, an attempt has been made to examine the strategies adopted for enrolling girls by different agencies in Gujarat and to see whether the neediest and the deprived get enrolled in the scheme.